Motion and dosimetric criteria for selecting gating technique for apical lung lesions in magnetic resonance guided radiotherapy - Galetto, Matteo; Nardini, Matteo; Capotosti, Amedeo; Meffe, Guenda; Cusumano, Davide; Boldrini, Luca; Chiloiro, Giuditta; Romano, Angela; Votta, Claudio; Gambacorta, Maria A.; Indovina, Luca; Placidi, Lorenzo (Frontiers in Oncology, 2023)
Introduction: Patients treatment compliance increases during free-breathing (FB) treatment, taking generally less time and fatigue respect to deep inspiration breath-hold (DIBH). This study quantifies the GTV motion on cine-MRI of apical lung lesions undergoing a SBRT in a MR-Linac and supports the patient specific treatment gating pre-selection. Material and methods: Twelve patients were retrospectively enrolled in this study. During simulation and treatment fractions, sagittal 0.35T cine-MRI allows real-time GTV motion tracking. Cine-MRI have been exported, and a in house developed MATLAB script perform image segmentation for measuring GTV centroid position on cine-MRI frames. Motion measurements were performed during the deep inspiration phase of DIBH patient and during all the session for FB patient. Treatment plans of FB patients were reoptimized using the same cost function, choosing the 3mm GTV-PTV margin used for DIBH-patients instead of the original 5mm margin, comparing GTV and OARs DVH for the different TP. Results: GTV centroid motion is less than 2.2mm in the antero-posterior and cranio-caudal direction in DIBH. For FB-patients GTV motion is lower than 1.7mm, and motion during the treatment was always in agreement with the one measured during the simulation. No differences have been observed in GTV coverage between the TP with 3mm and 5mm margins. Using 3mm margin the mean reduction in chestwall and trachea-bronchus Dmax was 2.5Gy and 3.0Gy respectively, and a reduction of 1.0Gy, 0.6Gy and 2.3% in Dmax, Dmean and V5Gy of homolateral lung, and 1.7Gy in contralateral lung Dmax. Discussions: Cine-MRI allows to select FB lung patients when GTV motion is less than 2mm. The use of narrower PTV margins, reduces OARs dose and maintains target coverage.